Analisis Ciri-Ciri, Makna dan Fungsi Pantun Masyarakat Kaur Provinsi Bengkulu Relevansinya dengan Pembelajaran Pantun di SD - Dedi Apriansah; Abdul Muktadir; Irwan Koto (Universitas Bengkulu, 2023)
This study aims to analyze the characteristics, meaning and function of the rhymes of the Kaur community in their relevance to learning rhymes in elementary schools. The type of research used is qualitative and the research method used is descriptive. The research subjects consisted of two community leaders and one head of the Kaur customary institution. Data collection techniques used in this study were interviews with informants and documents. The research instrument used was an interview guide sheet. The research results collected 69 poems of the Kaur community which were obtained from informants and documents. Of the 69 rhymes, there are 10 rhymes which mean expressions of advice, 7 rhymes mean expressions of satire, 3 rhymes mean expressions of advice or advice, 9 rhymes mean expressions of happiness and 33 rhymes mean expressions of sadness and 7 rhymes mean expressions of humor. Of the 69 rhymes, there are 11 rhymes that have an educational function, 20 rhymes have a function of affection, 3 rhymes have a function of appreciation or gratitude, 23 rhymes have a function of language intelligence and 12 rhymes have an entertainment function. Based on the 2013 curriculum for class V semester I, there is relevance for learning pantun in elementary schools at KD 3.6 and KD 4.6.